2010
DOI: 10.1002/pen.21679
|View full text |Cite
|
Sign up to set email alerts
|

Observation of instabilities in flow front during micro injection molding process

Abstract: This work has investigated filling characteristics during injection molding of a thin‐plate with microchannel patterns on it. To conduct molding experiments, an injection mold and mold inserts with microchannel patterns were designed and built. The experiments were conducted for three different channel sizes, and the results are analyzed. An unstable filling flow was observed in microscopic images for the smallest channel size. The front advanced with continuous creation and merge of microballs, which looked l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…The microscale rheological properties at a high shear rate, critical stress for wall slip, and so on are required for better process simulation [ 57 , 58 ]. The strong elastic effect, especially at the locations where an abrupt change of channel geometry occurs, and the onset of the flow instability due to channel dimension [ 59 ] need to be taken into consideration. Different polymers were used to make microdevices through microinjection molding, such as PMMA [ 60 ], PS [ 61 , 62 , 63 , 64 ], PP [ 64 ], and COC [ 64 , 65 ].…”
Section: Mold-based Techniquesmentioning
confidence: 99%
“…The microscale rheological properties at a high shear rate, critical stress for wall slip, and so on are required for better process simulation [ 57 , 58 ]. The strong elastic effect, especially at the locations where an abrupt change of channel geometry occurs, and the onset of the flow instability due to channel dimension [ 59 ] need to be taken into consideration. Different polymers were used to make microdevices through microinjection molding, such as PMMA [ 60 ], PS [ 61 , 62 , 63 , 64 ], PP [ 64 ], and COC [ 64 , 65 ].…”
Section: Mold-based Techniquesmentioning
confidence: 99%
“…The complex filling field can affect the crystallization phase, which can be seen from the huge difference of the proportion of the skin and core layer in the “skin–core” structure for semi-crystalline materials [ 26 ]. For semi-crystalline materials, physical properties, such as mechanical, optical, electrical, and chemical properties, mainly depend on the crystalline morphology of the materials [ 27 ].…”
Section: Ultrasound-assisted Micro-injection Moldingmentioning
confidence: 99%
“…Further research on IM parts with micro channels with widths of 30, 60, and 100 µm concluded that using optimum settings for mould temperature and hold pressure, the channels were completely replicated whilst a higher injection pressure caused excessive stress during demoulding [19,20].…”
Section: The Effects Of Process Conditions On Part Demouldingmentioning
confidence: 99%